2008
DOI: 10.1149/1.2839606
|View full text |Cite
|
Sign up to set email alerts
|

Partially Oxidized Tantalum Carbonitrides as a New Nonplatinum Cathode for PEFC–1–

Abstract: Partially oxidized TaC0.58normalN0.42 has been investigated as a cathode for polymer electrolyte fuel cells (PEFCs). Catalytic activity for the oxygen reduction reaction (ORR) significantly depends on the oxidation state of TaC0.58normalN0.42 . TaC0.58normalN0.42 and Ta2normalO5 had a poor catalytic activity for the ORR. The onset potential on the partially oxidized TaC0.58normalN0.42 for the ORR had a maximum value of 0.83 V vs a reversible hydrogen electrode in 0.1moldm−3 normalH2SO4 at 30°C . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 51 publications
1
79
0
Order By: Relevance
“…In particular, we found that the partially oxidized TaC 0.58 N 0.42 powder had a definite catalytic activity for the ORR and the mixture with the carbon black as a current collector was useful to increase the ORR current [16]. However, the characterization of the specimens and the discussion of the correlation between the physical properties and the catalytic activity for the ORR had not sufficiently performed yet.…”
Section: Introductionmentioning
confidence: 93%
“…In particular, we found that the partially oxidized TaC 0.58 N 0.42 powder had a definite catalytic activity for the ORR and the mixture with the carbon black as a current collector was useful to increase the ORR current [16]. However, the characterization of the specimens and the discussion of the correlation between the physical properties and the catalytic activity for the ORR had not sufficiently performed yet.…”
Section: Introductionmentioning
confidence: 93%
“…Although the high ORR catalytic activity of tantalum oxynitrides and related compounds has already been reported by other research groups [16][17][18][19][20], significantly high activity of TaO x containing no nitrogen or carbon for the reaction has not yet been reported. The E ORR of the Ta 2 O 5 powder prepared at 1000ºC by Ota's research group was about 0.5 V vs. RHE.…”
Section: Orr Activity Of Tao X Powder Prepared From the Dip-coating Smentioning
confidence: 92%
“…Various approaches have been taken to overcome these problems, with a particular focus on searching for suitable non-platinum elements, including oxides [6][7][8][9], carbides [10], nitrides, silicides, metal complexes [11,12], and other compounds [13][14][15]. Recently, some interesting studies were reported on the development of Pt-free oxide cathodes, such as Ta-O-N, Ta-C-N-O, and Nb-C-N-O [16][17][18][19][20][21]. In previous investigations [8,9], we reported the ORR activity of dip-coated IrO 2 /Ti catalyst electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the electrocatalytic activity for the oxygen reduction reaction (ORR) on Pt-based electrocatalysts is insufficient to obtain the required efficiency. It is mostly because of the considerable over-potential losses (0.3-0.4 V) of this reaction in the cell operating conditions [13]. Furthermore, natural resources of Pt are scarce and highly expensive.…”
Section: Introductionmentioning
confidence: 99%